The Non Governmental Organizations and its relationship with Human Development (Mayéutica Revista Científica de Humanidades y Artes, 2017)
In this essay, we make an exercise of conceptual linking between the paradigm of Human Development and the role of Non Governmental Organizations (NGO). Its purpose is to present the conceptual theoretical tendencies on Human Development and NGOs that give way to the consolidation of the social net, contribute to strengthen democracy, subscribe to social participation and build networks of citizens based on Social Capital. Among the reflections highlights the relationship between the expansion of opportunities and freedoms raised in the Human Development paradigm that considers people as the center of development to expand opportunities for them to achieve their valuable objectives in contexts of equity, sustainability and participation, in which somehow NGOs are linked as instances capable of uniting actors of civil society in order to reach common goals.
Keywords: non-governmental organizations; human development; social capital; liberties; capabilities